Mars Science Laboratory CheMin Data From the Glen Torridon Region and the Significance of Lake‐Groundwater Interactions in Interpreting Mineralogy and Sedimentary History. Issue 11 (3rd November 2022) - Thorpe, Michael T.; Bristow, Thomas F.; Rampe, Elizabeth B.; Tosca, Nicholas J.; Grotzinger, J. P.; Bennett, K. A.; Achilles, C. N.; Blake, D. F.; Chipera, S. J.; Downs, G.; Downs, R. T.; Morrison, S. M.; et al.
Abstract: The Glen Torridon (GT) region in Gale crater, Mars is a region with strong clay mineral signatures inferred from orbital spectroscopy. The CheMin X‐ray diffraction (XRD) instrument onboard the Mars Science Laboratory rover, Curiosity, measured some of the highest clay mineral abundances to date within GT, complementing the orbital detections. GT may also be unique because in the XRD patterns of some samples, CheMin identified new phases, including: (a) Fe‐carbonates, and (b) a phase with a novel peak at 9.2 Å. Fe‐carbonates have been previously suggested from other instruments onboard, but this is the first definitive reporting by CheMin of Fe‐carbonate. This new phase with a 9.2 Å reflection has never been observed in Gale crater and may be a new mineral for Mars, but discrete identification still remains enigmatic because no single phase on Earth is able to account for all of the GT mineralogical, geochemical, and sedimentological constraints. Here, we modeled XRD profiles and propose an interstratified clay mineral, specifically greenalite‐minnesotaite, as a reasonable candidate. The coexistence of Fe‐carbonate and Fe‐rich clay minerals in the GT samples supports a conceptual model of a lacustrine groundwater mixing environment. Groundwater interaction with percolating lake waters in the sediments is common in terrestrial lacustrine settings, and the diffusion of two distinct water bodies within the subsurface can create a geochemical gradient and unique mineral front in the sediments. Ultimately, the proximity to this mixing zone may have controlled the secondary minerals preserved in sedimentary rocks exposed in GT. Plain Language Summary: The Glen Torridon (GT) region on the lower slopes of the sedimentary mound in Gale Crater, Mars is characterized by terrains with enhanced clay mineral spectral signatures, as identified from orbit. This regional distinction in the landscape was confirmed on the ground with some of the highest clay mineral abundances measured to date by the CheMin X‐ray diffraction instrument onboard the Mars Science Laboratory rover, Curiosity . In addition to clay minerals, this region is unique because of two new phase identifications for CheMin: (a) Fe‐carbonates, which have been previously suggested from other instruments onboard Curiosity, but definitively identified for the first time with CheMin and (b) a new phase that has never been detected before on Mars. Even on Earth, few examples of this enigmatic phase exist, but here we modeled a mixture of clay minerals that were able to replicate the novel CheMin observations. Conceptually, a lake environment that interacts with discharging groundwater in the subsurface is an ideal setting to form the observed mineralogical trends in the GT region. Ancient lake and ground waters would have been geochemically distinct and the mixing of these water bodies in the sediments would have created unique mineralogical zones in the subsurface. Key Points: Mineralogical overview of the Glen Torridon region, Gale crater, Mars The Glen Torridon region is enriched in clay minerals and has a unique secondary mineral assemblage Lacustrine‐groundwater mixing model is used to conceptualize regional variability and overall sedimentary history